Sintesis Metil Ester Sulfonat dari Sulfonasi Metil Ester Minyak Sawit dengan Agen Na2S2O5 - Nur Asma Deli (Departement of Mathematics Education, 2023)
Surfactants are surface active ingredients that function to reduce the surface tension of a liquid. In general, surfactants are synthesized from petroleum and natural gas derivatives, but they can cause environmental pollution and are not renewable, so an alternative raw material is needed, namely palm oil. One type of surfactant that can be produced from palm oil is methyl ester sulfonate (MES). This study aims to obtain the optimum process conditions and the characteristics of the MES surfactant produced from palm oil methyl ester with the sulfonating agent Na2S2O5. The preparation of methyl esters was carried out in two stages of esterification and transesterification reactions using methanol as a source of alcohol with H2SO4 as an acid catalyst and NaOH as a base catalyst. Sulfonation was carried out at temperatures of 80, 90 and 100 0C, the ratio of methyl ester to Na2S2O5 was 1:0.5; 1:0.75; 1:1 and 5 hours reaction time. The optimum process was obtained by treating the temperature of 90 0C with a mole ratio of Na2S2O5 to methyl ester 1:1 with a reaction time of 5 hours. The MES characteristics resulting from these conditions had a pH of 1.45, an acid number of 10.6 mgKOH/g, a density of 0.886 g/cm3 and a sulfonate absorbance value of 0.290.